Strategic Alliance, Operations & Partnership at Lodha - Gorasia, Jahnvi (ATLAS SkillTech University, 2024)
During my two-month internship at Lodha, I had the unique opportunity to play a crucial role in the strategic alliance, operations, and partnership division. One of my key responsibilities was acquiring new clients for the application being developed, which featured a marketplace for prominent brands. Over the course of my internship, I successfully handled approximately 75 esteemed brands, handling end-to-end processes, from initial contact to formalities and seamless brand integration.
Project Report on Strategic Alliance, Operations & Partnership at Lodha (2022-24) Under the Guidance of Prof. Ameya Ambulkar